Enhanced Recovery After Surgery as an auditing framework for identifying improvements to perioperative nutrition care of older surgical patients. Issue 6 (June 2018) - Byrnes, Angela; Banks, Merrilyn; Mudge, Alison; Young, Adrienne; Bauer, Judy
Abstract Older patients are at increased risk of malnutrition and reduced physical function. Using Enhanced Recovery After Surgery (ERAS) guidelines as an auditing framework, this study aimed to determine adherence of nutrition care to perioperative best practice in older patients. A single researcher retrieved data via chart review. Seventy-five consenting patients ≥65 years (median 72 (range 65–95) years, 61% male) admitted postoperatively to general surgical wards were recruited. Sixty per cent had a primary diagnosis of cancer and 51% underwent colorectal resection. Seventeen per cent and 4% of patients met fasting targets of 2–4 h for fluid and 6–8 h for food, respectively. Fifty-five per cent were upgraded to full diet by first postoperative day. Nil received preoperative carbohydrate loading. Minimally invasive surgery (p  = 0.01) and no anastomosis formation (p  = 0.05) were associated with receiving ERAS-concordant nutrition care. This study highlights areas for improvement in perioperative nutrition care of older patients at our facility.